Congenital segmental dilatation of intestine with different morphology: A case report - Mirza, Muhammad Bilal; Maham, Sumaira Noor; Talat, Nabila (Journal of Neonatal Surgery, 2021)
Background: Congenital segmental dilatation of intestine is a rare entity characterized by a localized dilated segment of the intestine. It manifests as neonatal intestinal obstruction. Occurrence with another surgical anomaly may masquerade it and complicate the treatment course. Case Presentation: A 1-day-old male neonate with anorectal malformation underwent colostomy as first stage of the treatment. The stoma did not function postoperatively. At repeat surgery, congenital segmental dilatation of the ileum, with slightly different morphology, was found. Resection of the lesion and ileostomy were formed. Postoperative course remained uneventful. Conclusion: Congenital segmental dilatation of intestine may be missed at initial surgery. Complete surgical resection is curative.